(untitled) (Fisioterapia e Pesquisa, 2002)
Anorexia nervosa is an cating diseorder characterized by a deliberate weight loss induced or kept by patient. It occurs eight times mores in women than in men and it is beggining is associated to a particular age group (at adolescence, when "diet manias " begin) to factors concerning to subject´s appearance or to certain professional activities such as dancers, models, etc.